An econometric model for evaluating success/failure of an R&D project: the case of Korea. (1st January 2011) - Lee, Johng-Ihl
The financial crisis in 1997, which led Korea to the IMF management system, had offered the realisation of the technological competitiveness, owing to the significant increase of the government R&D budget from 3.5 trillion won in 1999 to 12 trillion in 2009. This paper examines the impact of government R&D incentives on the technological outcome by analysing firms' investment behaviours subject to the Korea's technology development program. Based on a mathematical model considering uncertainty and consequently introduced hypotheses, an econometric model of technological outcomes is estimated on a project level with cross-sectional data from Korea's R&D program. With a single equation approach, it is found that the structure of investment is a far more significant factor than the total amount of investment and that cash investment is a positive factor and in-kind for negative. The larger the number of institutions involved in a project, the less likely it leads to success, and meeting the proposed deadlines without postponing is estimated to be a good barometer to predict the successful outcome of an R&D project.